Tuning intramolecular charge transfer and spin–orbit coupling of AIE-active type-I photosensitizers for photodynamic therapy. Issue 32 (3rd August 2022) - Singh, Ravinder; Chen, Deng-Gao; Wang, Chun-Hsiang; Wu, Chi-Chi; Hsu, Chao-Hsien; Wu, Chi-Hua; Lai, Tai-Ying; Chou, Pi-Tai; Chen, Chao-Tsen
Abstract : Judicious strategy to envision fine-tuning of intramolecular charge transfer (ICT) and spin-orbit coupling (SOC) features for the advances of AIE-active Type-I photosensitizers (PSs) for image-guided photodynamic therapy (PDT). Abstract : Development of photosensitizers (PSs) featuring type-I reactive oxygen species (ROS) with aggregation-induced emission (AIE) properties is a judicious approach to overcome the deficit of conventional photodynamic therapy (PDT). However, it remains a challenge to design AIE-active type-I ROS PSs using a simple theranostic scaffold paired with a delicate balance between intramolecular charge transfer (ICT) and large spin–orbit coupling (SOC) features to facilitate intersystem crossing (ISC) and hence to intensify triplet excitons for type-I ROS generation as well as to improve optical properties for the desired biomedical applications. In this work, a rationally designed series of PSs based on C-6-substituted tetraphenylethylene-fused benzothiazole-coumarin scaffolds, named TPE- n CUMs, were synthesized via a fused-ring-electron-acceptor (FREA) strategy, endowed with AIE properties in aqueous solution and thus self-monitoring type-I ROS generation under white-light irradiation to study the effects of diverse ICT and SOC potentials on their photochemical and optical properties. Both experimental and theoretical results revealed that the concomitantly increasing strengths of both ICT and SOC features promote type-I ROS generation by TPE- n CUMs . The key role of the SOC-promoting carbonyl group towards the ROS generation ability of TPE- n CUMs was then examined. Among TPE- n CUMs, gem -2OMe-TPE-2CUM displayed highly efficient type-I ROS generation. Importantly, gem -OMe-TPE-1CUM acts as a fluorescent indicator in HeLa cells ( in vitro ), revealing its excellent diffusion capability in both lysosomal and mitochondrial organelles with low dark toxicity, high cytotoxicity under white-light and remarkable PDT efficiency. Our study has thus elucidated a rationally designed strategy at the molecular level to fine-tune ICT and SOC features for the advance of AIE-active type-I ROS PSs, opening a new avenue for cancer treatment and image-guided therapy.